Highly Efficient Bifunctional Amide Functionalized Zn and Cd Metal Organic Frameworks for One-Pot Cascade Deacetalization–Knoevenagel Reactions - Karmakar, Anirban; Paul, Anup; Rúbio, Guilherme M. D. M.; Soliman, Mohamed M. A.; Guedes da Silva, M. Fátima C.; Pombeiro, Armando J. L. (Frontiers in Chemistry, 2019)
A pyridine based amide functionalized tetracarboxylic acid, 5,5'-{(pyridine-2,6-dicarbonyl)bis(azanediyl)}diisophthalic acid (H4L), was synthesized and its coordination chemistry towards zinc(II) and cadmium(II) ions was studied. The reactions of H4L with Zn(NO3)2.6H2O and Cd(NO3)2.4H2O led to its full or partial deprotonation, respectively, and the formation of the 2D coordination polymers [Zn2(L)(H2O)4]n.4n(H2O) (1) and [Cd3(HL)2(DMF)4]n.4n(DMF) (2) (DMF = N,N’-dimethylformamide), respectively. They were characterized by elemental analysis, FT-IR, photoluminescence, thermogravimetry, and single-crystal and powder X-ray diffraction. In 1, the L4- ligand is planar with every carboxylate anion binding a Zn(II) cation and giving rise to a 2D grid with the metals with tetrahedral environments. In 2 the combination of bridging HL3- and dimethylformamide to form trinuclear Cd(II) clusters engenders secondary building block units and generates a layered type 2D network with the metals with octahedral and pentagonal bipyramid coordination geometries. The topological analyses of 1 and 2 reveal 2,4-connectd and 3,6-connected binodal nets, respectively. On account of the presence of Lewis acid (Zn or Cd centers) as well as basic (uncoordinated pyridine and amide groups) sites, 1 and (to a much lower extent) 2 effectively catalyze the one-pot cascade deacetalization−Knoevenagel condensation reactions, under considerably mild conditions. They act as heterogeneous catalysts, being easy to recover and recycle, without losing activity.